Optical control of endogenous receptors and cellular excitability using targeted covalent photoswitches - Mercè Izquierdo-Serra (Nature Portfolio, 2016)
Biological activity can be photoswitched by light-regulated drugs, but so far only diffusible ligands have been shown to work on endogenous receptors. Here the authors develop targeted covalent photoswitches that couple to a protein target by ligand affinity, and demonstrate photocontrol of GluK1-expressing neurons.